PEMBELAJARAN PASSING BAWAH BOLA VOLI MINI MENGGUNAKAN PERMAINAN BOLA GANTUNG (Department of Physical Education, Sport, Health and Recreation, 2013)
The purpose of this study was to determine the improvement of learning outcomes passing under a mini volleyball game using a ball hanging on Elementary School fourth grade students Srengseng 03 districts pagerbarang tegal district . This study conducted in four stages , including planning , action , observation , and reflection using the classroom action research . Each meeting shows the stages of the process of learning the material physical education volleyball . The subjects were fourth grade students of the District 03 Elementary School Srengseng Pagerbarang Tegal in 2013 numbered 20 students . The results based on the analysis of the percentage of cycle 1 and cycle percentage 55 % 85% 2 30% increase in the percentage of successful assessment of indicators of success that is expected is 85 % . Conclusion of this study indicate that the hanging ball games can improve learning passing under mini volleyball in grade IV elementary School District of Pagerbarang Srengseng 03 Tegal regency . Teachers Penjasorkes suggestions in carrying out the task of teaching should always carry out action research as a factor if there are problems inhibiting the learning process .